Insects by the numbers : a book of infographics - Jenkins, Steve, 1952- (Jenkins, Steve, 1952- By the numbers., 2020)
Through infographics and illustrations readers will learn about the sometimes gross and absolutely always fascinating world of insects. With astounding numbers, facts, and figures, discover some of the most astonishing aspects of the animals that outnumber us humans on the planet: bugs!